2016
DOI: 10.1073/pnas.1603956113
|View full text |Cite
|
Sign up to set email alerts
|

Reducing uncertainties in decadal variability of the global carbon budget with multiple datasets

Abstract: Conventional calculations of the global carbon budget infer the land sink as a residual between emissions, atmospheric accumulation, and the ocean sink. Thus, the land sink accumulates the errors from the other flux terms and bears the largest uncertainty.Here, we present a Bayesian fusion approach that combines multiple observations in different carbon reservoirs to optimize the land (B) and ocean (O) carbon sinks, land use change emissions (L), and indirectly fossil fuel emissions (F) from 1980 to 2014. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Posterior FR shows a significantly declining trend over the entire period ( p < 0.05) at a rate of −0.019 PgC yr −2 . The uncertainty reductions for F, O, and B + L (Figures c and d) are similar with those obtained by Li et al (), who used the same observational constraints for net fluxes.…”
Section: Resultssupporting
confidence: 87%
“…Posterior FR shows a significantly declining trend over the entire period ( p < 0.05) at a rate of −0.019 PgC yr −2 . The uncertainty reductions for F, O, and B + L (Figures c and d) are similar with those obtained by Li et al (), who used the same observational constraints for net fluxes.…”
Section: Resultssupporting
confidence: 87%
“…Keenan et al () suggested that both a slower increase in terrestrial ecosystem respiration (TER) and a continued increase in global gross primary production (GPP) explain the increased S LAND and the pause in the CGR during 1998–2011. Like many previous studies, the land carbon sink in these studies was inferred as the residual land sink, which may be indirectly affected by uncertainties in estimation of E FF , ocean sink, and land use change (LUC) emissions (Arneth et al, ; DeVries et al, ; Li et al, ; Pongratz et al, ). The relative contributions of different ecological processes to the acceleration of S LAND remain uncertain.…”
Section: Introductionmentioning
confidence: 91%
“…Correspondence to: S. Piao, slpiao@pku.edu.cn Li et al, 2016;Pongratz et al, 2014). The relative contributions of different ecological processes to the acceleration of S LAND remain uncertain.…”
Section: Supporting Informationmentioning
confidence: 99%
“…With a third of CO 2 emissions absorbed by global terrestrial ecosystems, the buildup of atmospheric CO 2 is abated (Le Quere et al, 2015). Yet the magnitude and regional distribution of the terrestrial carbon (C) sink at elevated CO 2 levels remain uncertain, due to our limited knowledge on vegetation responses to increased CO 2 concentration and nutrient limitation (Bellassen & Luyssaert, 2014;Grassi et al, 2017;Le Quere et al, 2009;Le Quere et al, 2015;Li et al, 2016;Schimel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%